Aldosterone‐producing adrenocortical carcinoma with myxoid differentiation in a cat. (21st September 2018) - Attipa, Charalampos; Beck, Samuel; Lipscomb, Victoria; English, Kate; Carvalho, Sofia; Kiupel, Matti; Szladovits, Balázs; Peters, Laureen M.
Abstract: A 10‐year‐old male neutered Persian cat was presented with an abdominal mass and history of weakness. Blood smear examination found marked elliptocytosis, and serum biochemical analysis revealed hypokalemia, hypochloremia, increased creatine kinase activity, and a high aldosterone concentration. Cytologic examination of the mass revealed neoplastic endocrine cells with moderate criteria of malignancy, favoring adrenocortical neoplasia. The adrenal mass was surgically excised and histologically characterized by lobules of mildly pleomorphic, polygonal neoplastic cells with moderate to abundant, occasionally granular, eosinophilic cytoplasm. Lobules were separated by fine fibrovascular trabeculae, and numerous cystic cavities containing amorphous eosinophilic material that stained positive with Alcian blue and periodic acid‐Schiff were seen. Neoplastic cells were multifocally positive for cytochrome P450 aldosterone synthase. Based on clinicopathologic and immunohistochemical findings the present case was diagnosed as an aldosterone‐producing adrenocortical carcinoma with myxoid differentiation. While this entity has not been reported in cats, myxoid differentiation of adrenocortical carcinomas has been found in other species and can pose a major diagnostic challenge on microscopic examination.